ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN AKUNTANSI PADA SKPD KOTA KEDIRI - Downida, Antok Noven; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to test and to analyze the empirical influence of internal control, obedience onaccounting rules, and asymmetric information to the tendency of accounting fraud. The population is FinancialManagement Officer (PPK) at the Local Apparaturs Working Unit (SKPD) and Regional FinancialManagement Working Unit (SKPKD) in Kediri.The data collection technique has been done by issuingquestionnaires.This research is quantitative research is research that focuses on testing hypothesis wit statisticalmethod analysis tools and produce results that can be generalized. The data is the primary data which has beencollected by issuing questionnaires to the respondents.This study uses assumption test normalias klasaik is test,test multicoloniarity and heteroscedasticity test. The data source is the opinions and perceptions of eachpersonnel within the government agency responsible for making or preparing financial reports. The researchmethod has been conducted by using quantitative method. The data analysis technique has been done by usingmultiple linear regressions analysis.Based on the result of the research, it has been found that internal controland obedience on accounting rules has negative influence to the tendency of accounting fraud. Meanwhile,asymmetric information has positive influence to the tendency of accounting fraud.Keywords: Internal control, obedience on accounting rules, asymmetric information, tendency of accountingfraud